Law No. 79 for Year 2016 On Settlement of Tax Disputes Amended By Laws Nos. 14-174/2018, 16-173/2020, And 153/2022 = قانون رقم 79 لسنة 2016 فى شأن إنهاء المنازعات الضريبية المعدل بالقوانين أرقام 14-174/2018 و 16-173/2020 و 153/2022 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic